Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

A man notices two objects in a straight line due west. After walking a distance c due north he observes that the objects subtend an angle α at his eye; and , after walking a further distance 2c due north, an angle β. Show that the distance between the objects is 8c/3 cot β – cot α ; the height of the man is being ignored.

A man notices two objects in a straight line due west. After walking a distance c due north he observes that the objects subtend an angle α at his eye; and , after walking a further distance 2c due north, an angle β. Show that the distance between the objects is 8c/3 cot β – cot α ; the height of the man is being ignored.

Grade:10

1 Answers

Jitender Pal
askIITians Faculty 365 Points
7 years ago
Hello Student,
Please find the answer to your question
Let the man initially be standing at ‘A’ and ‘B’ be the position after walking a distance ‘c’, so total distance becomes 2c and the objects being observed are at ‘C’ and ‘D’.
235-579_12345.png
Now we have OA = c, AB = 2c
Let CO = x and CD = d
Let ∠CAD = α and ∠CBD = β
∠ACO = θ and ∠ADC = ϕ
∠BCD = ψ and ∠BCO = θ1
In ∆ ACO, tan θ = AO/CO ⇒ tan θ = c/x . . . . . . . . . . . . . . . . . . . . . . . . . (1)
In ∆ ADO, tan ϕ = c/x + d . . . . . . . . . . . . . . . . . . . . . . . . . . . . (2)
Now, θ = α + ϕ (Using ext. ∠ thm.)
⇒ α = θ - ϕ ⇒ tan α = tan (θ – ϕ) ⇒ = tan θ – tan ϕ/1 + tan θ tan ϕ
= c/x – c/x + d / 1 + c/d. c/x + d (using equations (1) and (2)
⇒ tan α = cx + cd – cx/x2 + dx + c2
⇒ x2 + c2 + xd = cd cot α . . . . . . . . . . . . . . . . . . . . . . . . . . . . . (3)
Again in ∆ ADO
tan ψ = 3c/x +d . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . (4)
tan θ1 = 3c/x . . . . . . . . . . . . . . . . . . . . . . . . . . . . . (5)
But θ1 = ψ + β (by text ∠ thrm)
⇒ β = θ1 – ψ
⇒ tan β = tan (θ1 – ψ) = tan θ1 – tan ψ/ 1+ tan θ1 tan ψ
⇒ tan β = \frac{\frac{3c}{x}-\frac{3c}{x+d}}{1+\frac{3c}{x}.\frac{3c}{x+d}}[ Using (4) and (5)]
⇒ tan β = 3cd/x2 + xd + 9c2
⇒ x2 + xd + 9c2 = 3cd cot β . . . . . . . . . . . . . . . . . . . . . . . . . . . . . (6)
From (3) and (6), we get
8c2 = 3cd cot β – cd cot α
⇒ d = 8c/3 cot β – cot α Hence proved.
Thanks
Jitender Pal
askIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free